Protein Modelling Insight to the Poor Sensitivity of Chikungunya Diagnostics on Indonesia’s Chikungunya Virus - Bevi Lidya; Umi Baroroh; Korry Novitriani; Bachti Alisjahbana; Iman Rahayu; Muhammad Yusuf; Toto Subroto (Universitas Gadjah Mada, 2023)
Sensitive detection of infectious diseases is crucial for effective clinical care. However, commercial rapid tests may be limited in their ability to detect pathogen variants across different countries. It was found that the sensitivity of a chikungunya rapid test on local strain was only 20.5% as compared to the East, Central, and South Africa (ECSA) phylogroup. Therefore, the development of geographically specific diagnostics is essential. Investigating the distinctive structural properties of a locally sourced antigenic protein is an important initiative for the development of a specific antibody. This study utilized structural bioinformatics and molecular dynamics simulations to investigate the differences between the E1-E2 antigenic proteins of the Indonesian chikungunya virus (Ind-CHIKV) and that of ECSA. The results showed that some of the mutation points are located at the antibody binding sites of Ind-CHIKV. G194S and V318R mutations were proposed as distinctive features of Ind-CHIKV, leading to weaker antibody binding compared to ECSA. It suggests that modifying the antibody to accommodate bulkier side chains at positions 194 and 318 could improve its effectiveness against Ind-CHIKV. These insights are valuable for developing a highly sensitive immunoassay for Ind-CHIKV and other regional pathogens, ultimately enhancing diagnostic capabilities in Indonesia.